2012
DOI: 10.2164/jandrol.112.016592
|View full text |Cite
|
Sign up to set email alerts
|

The Semen Quality of 1158 Men With Testicular Cancer at the Time of Cryopreservation: Results of the French National CECOS Network

Abstract: Testicular cancer is the most common cancer in young men. Several studies have reported an alteration in semen quality in nonseminoma tumors, but this result has not been confirmed in all of the published data. We performed a retrospective study in a population of 1158 men with testicular cancer who banked sperm between 1999 and 2003 in 11 French Centre d'Etude et de Conservation des Oeufs et du Sperme humain laboratories. Our study evaluated prefreeze and postthaw sperm parameters according to patient medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(61 citation statements)
references
References 43 publications
4
53
3
1
Order By: Relevance
“…Fertility preservation and paternity are significant issues in men diagnosed with testicular cancer (TC). Up to 50% of TC patients present with abnormal semen analysis at diagnosis (2,3). Furthermore, decreased fertility is well documented among survivors of TC (4,5).…”
mentioning
confidence: 99%
“…Fertility preservation and paternity are significant issues in men diagnosed with testicular cancer (TC). Up to 50% of TC patients present with abnormal semen analysis at diagnosis (2,3). Furthermore, decreased fertility is well documented among survivors of TC (4,5).…”
mentioning
confidence: 99%
“…Various mechanisms can contribute to semen impairment in testicular malignancy such as previous testicular disorders, tumor histology, stage of the disease and orchiectomy. 3 Damage of the spermatogenesis after treatment largely depends on the type of therapy and the gonadal function pretreatment. Norwegian population based study observed a 30% decrease in fertility among the cancer survivors when compared with the normal population.…”
Section: Discussionmentioning
confidence: 99%
“…According to a survey conducted by Molnar et al (19), sperm concentration is reduced in men exhibiting testicular tumors compared with matched healthy men. In a French national investigation, sperm concentration and total sperm number were significantly decreased in NSGCT patients following orchiectomy, therefore sperm cryopreservation should be considered prior to orchiectomy (21). In a number of retrospective studies (22)(23)(24), sperm cryopreservation has been recommended for testicular cancer patients who intend to have a child in the future.…”
Section: Discussionmentioning
confidence: 99%